Preparing Learners for the Innovation Economy: It’s time to rethink almost everything about technology education - Seemann, Kurt (Design and Technology Education: An International Journal, 2006)
Have you ever noticed that when the economy shows strong growth in job creation, the stock market often drops, when jobs are slashed by as many as thousands or that when a company invests in new labour replacing technology in its production, the stock value of the companies involved rises (Chasan, 2006; Isidore, 2005)? Despite all the efforts to produce skilled people in traditional fields, the tide of sustainable employment in those areas, appears to be structurally prohibitive raising basic questions of whether traditional perceptions of Technology in school curriculum remains viable and whether a rethink of why Technology ought be taught is now due for a new discourse. In our complex new world, the one right here and now and unfolding outside the school gate, we ought cast forward and rethink the new opportunities before us with Technology studies as a subject in waiting. This paper explores the proposition that, in the context of understanding the role of innovation and knowledge in the world economy, it may be time to completely rethink the role of Technology in schooling as having a unique purpose in the curriculum. One that is characterised by its focus on graduate attributes rather than specific traditional equipment skilling expressed in the finish of ‘objects’ and by its responsive behaviour to a modern world economy, with complex social and ecological pressures.